Sherlock Holmes : the complete novels and stories - Doyle, Arthur Conan (New York : Bantam Dell, 2003)
John F. Kennedy Center for the Performing Arts, the Kennedy Center by arrangement with the governors of the Royal Shakespeare Theatre, Stratford-Upon-Avon, England, James Nederlander, Inc., The Shubert Organization, Kennedy Center Productions, Inc., Adela Holzer, Eddie Kulukundis, Victor Lurie presents The Royal Shakespeare Company with John Wood as "Sherlock Holmes," a play by Arthur Conan Doyle and William Gillette, and Philip Locke as Professor Moriarty, with Wendy Bailey, Arthur Blake, John Bott, Joseph Charles, Sean Clarke, Alan Coates, Robert Cook, John Keston, Barbara Leigh-Hunt, Joe Marcell, Mel Martin, Michael Mellinger, Pamela Miles, Martin Milman, Trevor Peacock, Tim Pigott-Smith, Nicholas Selby, Morgan Sheppard, Keith Taylor, Harry Towb, Michael Walker, music arranged by Michael Lankester, lighting designed by Neil Peter Jampolis, scenery and costumes designed by Carl Toms, directed by Frank Dunlop.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Sherlock Holmes; Theater programs -- Washington (D.C.); Theater programs -- 1974.; Playbills -- Washington (D.C.); Playbills -- 1974.